Variación temporal en la abundancia del rayador, Rynchops niger (Charadriiformes: Laridae) en Baja California Sur, México - Carmona, Roberto (Universidad de Costa Rica, 1995)
In 1992 and 1993 occurrence of the black skimmer Rynchops niger was recorded in Chametla and El Conchalito, La Paz Bay. There were 28 records in Chametla and 80 in El Conchalito; more in the smaller area perhaps because it has more resting sites. In 1992 the animals were in reproductive season, simultaneously with an "El Nino" phenomenon.